Application of Ultrasonic-Assisted Fractionation with Full-Factorial Design for the Production of Alkaloid-Rich Fraction from Ficus septica Leaves - Muhammad Hafizh Ridho; Andayana Puspitasari Gani; Subagus Wahyuono; Nanang Fakhrudin (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2020)
Ficus septica Burm. F (Awar-awar) in Indonesian herbal medicine traditionally used for the treatment of various disease. Previous studies indicated that the F. septica leaves contained phenantroindolizidine alkaloids with anticancer activity. Fractionation of the ethanol extract of F. septica leaves using n-hexane was able to separate chlorophylls and other inert non–polar constituents from the extract. This fractionation process can be optimized using ultrasonic-assisted fractionation to yield n-hexane insoluble fraction (HIF) that is rich in alkaloids. This study aimed to produce HIF from the ethanol extract of F. septica leaves by using optimized ultrasonic-assisted fractionation with n-hexane as a solvent and full factorial as experimental design. Ficus septica leaves were macerated in ethanol (60%) and the extract was used for the ultrasonic-assisted fractionation process. The duration of fractionation (5-30 minutes), the extract : n-hexane ratios (1:0.1 - 1:1.66 ml/ml), and the ultrasonic power (21-106 Wrms) were optimized to determine the optimal condition for each variable. These optimal variables were used for the production of HIF from the extract by using full factorial design in the ultrasonic-assisted fractionation process. The total alkaloid content was measured using spectrophotometry and was used as parameter for the optimization process. We found that the optimal condition for the fractionation process based on each single variable optimization were 5 minutes of the fractionation duration, 66-70Wrms of the ultrasonic power, and 1:0.7 - 1:0.8 of the extract : n-hexane ratio. By using these optimized variables, the ultrasonic-assisted fractionation using full factorial design yielded up to 0.035% total alkaloid content which is almost double from those in the extract (0.019%). This study provided a basic experimental model for the production of alkaloid-enriched HIF from F. septica leaves in the industrial or pilot scale, and might contribute to the development of Indonesian herbal medicine products from natural resources.